RNAi-Mediated Screening of Selected Target Genes Against Culex quinquefasciatus (Diptera: Culicidae). Issue 6 (1st July 2021) - Khalil, Sayed M S; Munawar, Kashif; Alahmed, Azzam M; Mohammed, Ahmed M A
Abstract: Culex quinquefasciatus, a member of the Culex pipiens complex, is widespread in Saudi Arabia and other parts of the world. It is a vector for lymphatic filariasis, Rift Valley fever, and West Nile virus. Studies have shown the deleterious effect of RNA interference (RNAi)-mediated knockdown of various lethal genes in model and agricultural pest insects. RNAi was proposed as a tool for mosquito control with a focus on Aedes aegypti and Anopheles gambiae . In this study, we examined the effect of RNAi of selected target genes on both larval mortality and adult emergence of Cx . quinquefasciatus through two delivery methods: soaking and nanoparticles. Ten candidate genes were selected for RNAi based on their known lethal effect in other insects. Disruption of three genes, chitin synthase-1, inhibitor of apoptosis 1, and vacuolar adenosine triphosphatase, resulted in the highest mortality among the selected genes using the two treatment methods. Silencing the other seven genes resulted in a medium to low mortality in both assays. These three genes are also active against a wide range of insects and could be used for RNAi-based mosquito control in the future.